Bile acids and vitamin A absorption in man: the effects of two bile acid-binding agents, cholestyramine and lignin - Barnard, D. L. (1973)
In 14 healthy volunteers, the addition of 12 g cholestyramine to a vitamin A-containing test meal reduced the expected rise in serum vitamin A by 59·5% (p<0·001). By contrast, lignin had no significant effect in 12 subjects. This study confirms the importance of bile acids in vitamin A absorption and the ineffectiveness of lignin as a sequestrator of conjugated bile acids.